2015
DOI: 10.1016/j.virol.2015.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Infectious Bursal Disease Virus non-structural protein VP5 is not a transmembrane protein

Abstract: Infectious Bursal Disease Virus (IBDV) causes a highly relevant poultry disease that affects young chickens causing, among other effects, immunosuppression. IBDV is a bi-segmented double stranded RNA virus. The smaller ORF of larger RNA segment encodes VP5, a 17-kDa non-structural protein. Although it is an important protein for viral replication cycle, the definition of its specific role and subcellular localization remains unclear. In the present work we demonstrate, using imaging techniques, that VP5 is not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 24 publications
(26 reference statements)
0
5
0
Order By: Relevance
“…However, it migrates as a 17-kDa product on SDS-PAGE, thus suggesting that it might be post-translationally modified [15]. Despite the lack of a transmembrane domain, VP5 accumulates at the cytosolic leaflet of different membranous cell compartments, preferentially at the plasma membrane (PM) [17, 18]. This tropism is mediated by the interaction of the VP5 C-terminal polycationic protein region, known as the phosphoinositide (PIP)-binding domain, with integral membrane PIPs [17].…”
Section: Introductionmentioning
confidence: 99%
“…However, it migrates as a 17-kDa product on SDS-PAGE, thus suggesting that it might be post-translationally modified [15]. Despite the lack of a transmembrane domain, VP5 accumulates at the cytosolic leaflet of different membranous cell compartments, preferentially at the plasma membrane (PM) [17, 18]. This tropism is mediated by the interaction of the VP5 C-terminal polycationic protein region, known as the phosphoinositide (PIP)-binding domain, with integral membrane PIPs [17].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, additional research is required to fully elucidate the roles of VP2 and VP5 in the virulence of IPNV infection. The VP5 sequence does contain the Bcl-2 homology (BH) domains BH1, BH2, BH3, and BH4 typical of class I and II Bcl-2 family proteins [ 21 , 22 ]. Accurate understandings on the role of these sequences in the cellular infection mechanism remain lacking, as is also the case for the functional effects of structural motif variations in VP5.…”
Section: Introductionmentioning
confidence: 99%
“…The literature reported that VP5 is a phosphoinositidebinding protein and demonstrated that VP5 protein is essential for the spread of the virus among cells (Méndez et al, 2015). Although topological prediction analysis revealed that VP5 protein may be a type II transmembrane protein, including potential transmembrane and intracellular N-terminal and C-terminal structures, the latest findings clearly indicate that VP5 is not a transmembrane protein (Carballeda et al, 2015). Therefore, the role of VP5 protein in the release of virions remains to be further studied.…”
Section: Vp5mentioning
confidence: 99%